Confidence in adaptive decision-making - Friedemann, M (2023)
The capacity for introspection and self-evaluation of our own thoughts and behaviours is a fundamental aspect of human cognition. Central to this faculty is the judgement of confidence in our beliefs and decisions, particularly in situations in which external feedback is sparse or absent. This thesis explores the critical role of confidence judgements in adaptive decision-making, substantiated by empirical research within the rigorously controlled environment of perceptual decision tasks. The first line of research probes the flexibility of confidence-guided information seeking behaviour. Findings illustrate a flexible interplay between confidence and information-seeking choices, contingent upon reward structures and the usefulness of information. However, the findings also unveil the boundaries of such flexibility, revealing a reliance on heuristic strategies, wherein a decrease in confidence generally prompts the need for more information, when dealing with more nuanced aspects of the choice environment. The second line of research investigates the context-sensitive role of confidence within social settings, uncovering distinct impacts of informational and normative social influences on confidence. The results indicate that in contexts devoid of feedback, individuals utilise others' confidence judgements as a benchmark to calibrate their own. Furthermore, under normative social influences, individuals strategically adapt their overt communication of confidence to suit the contextual demands. The third line of research examines the link between confidence biases and maladaptive behaviours, focusing on the example of problem gamblers. This inquiry reveals that problem gamblers display heightened decision confidence, yet concurrently exhibit reduced self-esteem compared to a control group. Such overconfidence may be a contributing factor to perpetuating gambling behaviours, which highlights the necessity of well-calibrated confidence for adaptive behaviour. Collectively, these research lines emphasise that confidence is a multifaceted, context-sensitive mechanism, playing a key role in guiding adaptive behaviour. This thesis highlights the pervasive influence of confidence across various facets of human life –– from everyday decision-making to psychopathology –– thereby underlining its vital role in adaptive decision-making.